Pathogenicity of Ebola and Marburg Viruses Is Associated With Differential Activation of the Myeloid Compartment in Humanized Triple Knockout-Bone Marrow, Liver, and Thymus Mice. (6th August 2018) - Lavender, Kerry J; Williamson, Brandi N; Saturday, Greg; Martellaro, Cynthia; Griffin, Amanda; Hasenkrug, Kim J; Feldmann, Heinz; Prescott, Joseph
Abstract: Ebola virus (EBOV) and Marburg virus (MARV) outbreaks are highly lethal, and infection results in a hemorrhagic fever with complex etiology. These zoonotic viruses dysregulate the immune system to cause disease, in part by replicating within myeloid cells that would normally innately control viral infection and shape the adaptive immune response. We used triple knockout (TKO)-bone marrow, liver, thymus (BLT) humanized mice to recapitulate the early in vivo human immune response to filovirus infection. Disease severity in TKO-BLT mice was dissimilar between EBOV and MARV with greater severity observed during EBOV infection. Disease severity was related to increased Kupffer cell infection in the liver, higher levels of myeloid dysfunction, and skewing of macrophage subtypes in EBOV compared with MARV-infected mice. Overall, the TKO-BLT model provided a practical in vivo platform to study the human immune response to filovirus infection and generated a better understanding of how these viruses modulate specific components of the immune system.